(untitled) (Research, Society and Development, 2024)
The amazon river The Amazon River basin is known for its great variety of vegetation and animals, as well as for the prominent cattle ranching. However, Amazonia hot and humid natural climate is a suitable environment for the development and spread of diseases, posing a challenge for the livestock sector. This study aimed to study livestock diseases in the northeastern Brazilian Amazon Region though a survey of tissue samples submitted to histopathological. A retrospective study was conducted in the archives of the Anatomical Pathology Sector of the Federal Rural University of Rio de Janeiro, Brazil, between 1997 and 2017. It was included tissue of bovine, bubaline, equine, ovine, and caprine collected in the Northeastern Brazilian Amazon Region and submitted to histopathological evaluation. Data on species, histologic description, and diagnosis were retrieved from the pathological reports, and ancillary techniques were applied to elucidate inconclusive cases. Between January 1997 and July 2017, 448 tissue samples were submitted for histopathological evaluation. Infectious diseases comprised 31.5% (141/448) of all diagnoses, followed by mineral imbalances (16.5%), neoplasia (10.7%), and poisonous plants and related conditions (8.9%). Histochemical, immunohistochemical and molecular techniques proved seem to be useful to help elucidate inconclusive cases.